Numerical modeling of a four-rod pumping scheme for improving TEM 00 -mode solar laser performance - Almeida, Joana (2019)
Financial support of the strategic project (UID/FIS/00068/2019) of the Science and Technology Foundation of Portuguese Ministry of Science, Technology and Higher Education (FCT-MCTES) is acknowledged. The fellowship Grant Nos. PD/BD/128267/2016, PD/BD/142827/2018, and SFRH/BPD/125116/2016 of Bruno D. Tiburcio, Dario Garcia, and Claudia R. Vistas, respectively, are also acknowledged.